Self-expanding metal stents (SEMS) for patients with advanced Esophageal cancer in Malawi: an effective palliative treatment - Thumbs, Alexander; Wilhelm, Torsten (Journal of surgical oncology, 2012)
Background and Objectives: Esophageal cancer is common in Malawi and most patients are inoperable at time of diagnosis. The aim of this study was to prospectively evaluate palliative treatment with self-expanding metal stents (SEMS) in Malawi, a low-income country with limited medical resources. Methods: Data of patients with advanced inoperable esophageal cancer were prospectively collected. Tumor and patient specifics, risk factors, dysphagia scores, complications, and survival were assessed. Follow-up data for 1 year or until death were collected from 118/143 patients (83%) during clinic visits, home visits, or via cell phone. Results: One hundred forty-three patients were treated with 154 SEMS. Median survival was 210 days (95% CI: 150-262 days). Fourteen of 118 patients with complete follow-up (11.9%) survived more than 1 year with longest documented survival of 406 days. The median dysphagia score improved from 3 at the time of presentation to 0 at the time of death. Early complications occurred in 4.2% (6/143), late complications in 11.9% of patients (14/118). The procedure related mortality was 2.1% (3/143). Conclusions: SEMS is an appropriate palliative treatment in a resource-limited environment. For the vast majority of patients a single intervention provides lasting improvement of dysphagia.
Gesehen am 24.05.2018
Article was first published online on 12 December 2011 in the Wiley Online Library